Level of awareness towards e-waste management / Rosilawati Sultan Mohideen … [et al.] - Sultan Mohideen, Rosilawati; Md Zin, Ahmad Muzzammil Aqib; Lokman, Nurul Akmal; Siswantini, Siswantini; Abdul Halim, Nurul Ashikin (Faculty of Communication & Media Studies, 2022)
Public consciousness around e-waste has always been at an all-time low even with countless efforts by the experts and activists constantly reminding them that mindless e-waste dumping would have their own consequences. Now that the issue has been constantly debated and the effects have started to show itself through the people it touched and the environment it slipped through, this research was made to identify if the people have started to learn more about e-waste and possess the awareness on how to manage it ethically. The research was made using a quantitative survey method through the distribution of Google Form on 300 volunteering respondents. The end of the research resulted in the respondents having shown quite a sufficient level of knowledge on the importance of e-waste management (M=3.33) and high level awareness towards the importance of e-waste management (M=3.51).